A new system for integrating information from libraries' catalogues to MODS format. (21st March 2008) - Fermoso, Ana Ma; Berjon, Roberto; Beato, Encarnacion; Mateos, Montserrat; Sanchez, Miguel; Manzano, Maribel; Gil, Ma
In this paper, we present the integration of information from library catalogues to the bibliographical format MODS (Metadata Object Description Schema). Hereby the resources of different bibliographical catalogues can be consulted obtaining the results in the same common format as MODS. To achieve our aim we use the XDS system, a software tool that solves the integration of heterogeneous data using XML as integration format. XDS allows integrating data from different relational and XML sources obtaining the results in the XML format specified by user. In this case the information sources store library catalogues and the output format is MODS.